Ifosfamide‐induced encephalopathy: Brand‐name (HOLOXAN®) vs generic formulation (IFOSFAMIDE EG®). (4th March 2019) - Chambord, Jeremy; Henny, Fabien; Salleron, Julia; Hombourger, Benoit; Lider, Pauline; Vigneron, Jean; Demore, Beatrice; Vallance, Catherine; Rios, Maria
Summary: What is known and Objective: Two forms of ifosfamide are commercially available in France: HOLOXAN® (brand‐name drug) and IFOSFAMIDE EG® (generic drug). Following the marketing launch of the generic drug, there has been a significant increase in cases of ifosfamide‐induced encephalopathy reported in France. Our objective is to compare the incidence of ifosfamide‐induced encephalopathy in adult patients treated with HOLOXAN® or IFOSFAMIDE EG®. Methods: This is a retrospective study of adult patients treated with ifosfamide in two medical centers from 2013 to 2017, with data analysed from medical records. Comparisons of patients were made, according to the formulation used and according to the occurrence of ifosfamide‐induced encephalopathy. The groups of patients were compared using a chi‐square or Fisher's exact test for qualitative parameters and a Wilcoxon test for quantitative parameters. To include confounding factors in the analysis of the impact of drug formulation on the occurrence of ifosfamide‐induced encephalopathy, a generalized linear model was performed with the occurrence of ifosfamide‐induced encephalopathy as the dependent parameter, and the formulation and the confounding factors as explanatory parameters. Results and Discussion: A total of 191 patients were included: 103 patients received HOLOXAN® (53.9%) and 88 patients received IFOSFAMIDE EG® (46.1%). In the HOLOXAN® group, the median infusion time was higher (12 hours vs 3h, P < 0.001) and aprepitant was administered more frequently (78.6% vs 69.7%, P < 0.001) than for the IFOSFAMIDE EG® group. Ifosfamide‐induced encephalopathy occurred in 11 patients (5.8%, CI 95% [2.9%, 10.0%]). In the ifosfamide‐induced encephalopathy group, median infusion time was higher (12 hours [12; 24] vs 3 hours [2; 12] P < 0.001) and a poor performance status was more frequent (54.5% vs 13.9%, P = 0.002) than in the group without ifosfamide‐induced encephalopathy. The frequency of ifosfamide‐induced encephalopathy in the HOLOXAN® group was 1.9% (2/103) against 10.2% (9/88) in the IFOSFAMIDE EG® group ( P = 0.014). Multivariate analysis revealed that treatment with IFOSFAMIDE EG® resulted in significantly more ifosfamide‐induced encephalopathies compared to HOLOXAN® (OR and CI 95%:7.4 [1.4; 39.5], P = 0.018). We identified two other risk factors for ifosfamide‐induced encephalopathy: long‐term infusion and a performance status of two or higher. What is New and Conclusion: The formation of chloroethylamine in solution could be the cause of more frequent ifosfamide‐induced encephalopathies with IFOSFAMIDE EG® compared to HOLOXAN®. Application of these data could help in the choice of ifosfamide formulation in adult patients to decrease the risk of ifosfamide‐induced encephalopathy, and more specifically for patients with risk factors. Abstract : Multivariate analysis revealed that the incidence of ifosfamide‐induced encephalopathy was approximately five times higher with the use of IFOSFAMIDE EG® (generic formulation of ifosfamide) compared with the use of HOLOXAN (brand name drug) (OR and CI 95% : 7.4 [1.4; 39.5], P = 0.018).